ANALISIS POLA PENGGUNAAN LAPTOP DAN HUBUNGAN ANTARA DURASI PENGGUNAAN LAPTOP DENGAN KEJADIAN WRIST PAIN - Ganis Maulasyifa (2020)
Background : Laptops have become a necessity for the community, especially students in daily life to help with work or just for recreation and laptops are considered more practical and efficient than other electronic devices. Because it has become a necessity, laptop users spend a long duration in their use. With continuous use added by the wrong usage patterns so that the posture becomes awkward will cause various musculoskeletal complaints, one of which is on the wrist. Objective: This study aims to determine whether there is a relationship between Pattern and Duration of Laptop Use Against Wrist Pain Complaints. This research method is a descriptive correlative research with cross sectional design. The population in semester 6 Physiotherapy Program Diploma Program Three students with a sample of 51 people. The parameters used are questionnaires and NRS, data analysis using statistical tests and hypotheses. Results : After processing the data obtained the results p = 0.0401 (p > 0.05) on the duration of the use of laptops against wrist pain complaints using the Chi-Square test. Conclusion: The results of the data show that the most frequent pattern of laptop use is 12 (27.5%) and there is no significant relationship between the duration of laptop use and wrist pain.